A sensitive bioanalytical method development and validation of cabozantinib in human plasma by LC-ESI-MS/MS (Brazilian Journal of Pharmaceutical Sciences, 2018)
A simple, sensitive and specific liquid chromatography–tandem mass spectrometry (LC-MS/MS) method was developed for the quantification of cabozantinib (CZ) in human plasma using cabozantinib-d4 (CZD4) as an internal standard (IS). Chromatographic separation was performed on Xbridge C18, 50 x 4.6 mm, 5 mm column with an isocratic mobile phase composed of 10mM Ammonium formate and Methanol in the ratio of (20:80 v/v), at a flow-rate of 0.7 mL/min. CZ and CZD4 were detected with proton adducts at m/z 502.2 → 391.1 and 506.3 → 391.2 in multiple reaction monitoring (MRM) positive mode respectively. Liquid-Liquid extraction method was used to extract the drug and IS. The method was validated over a linear concentration range of 5.0-5000.0 pg/mL with correlation coefficient (r2 ) ≥ 0.9994. This method demonstrated intra and inter-day precision within 1.95 to 2.37 and 2.93 to 9.3 % and Accuracy within 101.4 to 102.4 and 99.5 to 104.8 %. Cabozantinib was found to be stable throughout freeze-thawing cycles, bench top and postoperative stability studies.